West Bandung Regency Government's Strategy to Increase Public Reading Interest - Yuni Nurliana; Novie Indrawati Sagita; Neneng Yani Yuningsih (Journal of Public Representative and Society Provision, 2026)
Reading interest reflects the quality of human resources and the progress of a region's civilization. West Bandung Regency faces the challenge of low reading interest despite a high literacy rate. This study aims to analyze the local government's strategy in increasing public reading interest in 2024–2025. The method used is descriptive qualitative with a case study approach and Koteen's strategy theory including Corporate Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. The results of the study indicate the existence of literacy strengthening policies, implementation of mobile and digital libraries, cooperation with the private sector, and increasing the capacity of librarians. However, obstacles such as limited budget, infrastructure, and community participation are still obstacles. The conclusion of this study is that the implementation of strategies needs to be strengthened through cross-sector coordination, library service innovation, and the development of a technology-based literacy ecosystem.